Simplification of Algebraic Fractions

Here we will learn simplification of algebraic fractions to its lowest term.

1. Simplify the algebraic fraction:

\(\frac{8a^{2}b}{4a^{2}  +  6ab}\)

Solution:

\(\frac{8a^{2}b}{4a^{2}  +  6ab}\)

We see in the given fraction the numerator is monomial and the denominator is binomial, which can be factorized.

= \(\frac{\not{2}\times 2\times 2\times \not{a}\times a\times b}{\not{2}\not{a}(2a  +  3b)}\)

We can see that ‘2’ and ‘a’ are the common factors in the numerator and denominator so, we cancel the common factor ‘2’ and ‘a' from the numerator and denominator.

= \(\frac{4ab}{(2a  +  3b)}\)

 

2. Reduce the algebraic fraction to its lowest term:

\(\frac{x^{2}  +  8x  +  12}{x^{2}  -  4}\)

Solution:

\(\frac{x^{2}  +  8x  +  12}{x^{2}  -  4}\)

Each of the numerator and denominator is polynomial, which can be factorized.

= \(\frac{x^{2}  +  6x  +  2x  +  12}{(x)^{2}  -  (2)^{2}}\)

 = \(\frac{x(x  +  6 )  +  2(x  +  6)}{(x  +  2)(x  -  2)}\)

= \(\frac{(x  +  2)(x  +  6)}{(x  +  2)(x  -  2)}\)

We observed that in the numerator and denominator (x + 2) is the common factor and there is no other common factor. Now, we cancel the common factor from the numerator and denominator.

= \(\frac{(x  +  6)}{(x  -  2)}\)


3. Reduce the algebraic fraction to its lowest form:

\(\frac{5x^{2}  -  45}{x^{2}  -  x  -  12}\)

Solution:

\(\frac{5x^{2}  -  45}{x^{2}  -  x  -  12}\)

Each of the numerator and denominator is polynomial, which can be factorized.

= \(\frac{5(x^{2}  -  9)}{x^{2}  -  4x  +  3x  -  12}\)

= \(\frac{5[(x)^{2}  -  (3)^{2}]}{x(x  -  4)  +  3(x  -  4)}\)

= \(\frac{5(x  +  3)(x  -  3)}{(x  +  3)(x  -  4)}\)

Here, in the numerator and denominator (x + 3) is the common factor and there is no other common factor. Now, we cancel the common factor from the numerator and denominator.

= \(\frac{5(x  -  3)}{(x  -  4)}\)


4. Simplify the algebraic fraction:

\(\frac{x^{4}  -  13x^{2}  +  36}{2x^{2}  +  10x  +  12}\)

Solution:

\(\frac{5x^{2}  -  45}{x^{2}  -  x  -  12}\)

Each of the numerator and denominator is polynomial, which can be factorized.

= \(\frac{x^{4}  -  9x^{2}  -  4x^{2}  +  36}{2(x^{2}  +  5x  +  6)}\)

= \(\frac{x^{2}(x^{2}  -  9)  -  4(x^{2}  -  9)}{2(x^{2}  +  2x  +  3x  +  6)}\)

= \(\frac{(x^{2}  -  4)(x^{2}  -  9)}{2[x(x  +  2)  +  3(x  +  2)]}\)

= \(\frac{(x^{2}  -  4)(x^{2}  -  9)}{2(x  +  2)(x  +  3)} [Since, a^{2}  -  b^{2} = (a  +  b)(a  -  b)]\)

= \(\frac{(x  +  2)(x  -  2)(x  +  3)(x  -  3)}{2(x  +  2)(x  +  3)}\)

Here, in the numerator and denominator (x + 2) and (x + 3) are the common factors and there is no other common factor. Now, we cancel the common factors from the numerator and denominator.

= \(\frac{(x  -  2)(x  -  3)(x  -  3)}{2}\)


5. Reduce the algebraic fraction to its lowest term:

\(\frac{x^{2}  +  5x  -  2}{2x^{2}  +  x  -  6} \div \frac{4x^{2}  -  9}{6x^{2}  +  7x  -  3}\)

Solution:

\(\frac{x^{2}  +  5x  -  2}{2x^{2}  +  x  -  6} \div \frac{4x^{2}  -  9}{6x^{2}  +  7x  -  3}\)

Each of the numerator and denominator of each fraction are polynomial, which can be factorized.

Now by factorizing each polynomial we get;

3x2 + 5x – 2 = 3x2 –x + 6x – 2

                 = 3(3x – 1) + 2(3x – 1)

                 = (x + 2)(3x – 1)

2x2 + x – 6 = 2x2 - 3x - 4x - 6

                = x(2x – 3) + 2(2x – 3)

                = (x + 2)(2x - 3)

4x2 – 9 = (2x)2 - (3)2

           = (2x + 3)(2x – 3)

6x2 + 7x – 3 = 6x2 – 2x + 9x – 3

                  = 2x(3x – 1) + 3(3x – 1)

                  = (2x + 3)(3x – 1)

Therefore, we have

\(\frac{(x  +  2)(3x  -  1)}{(x  +  2)(2x  -  3)} \div \frac{(2x  +  3)(2x  -  3)}{(2x  +  3)(3x  -  1)}\)

= \(\frac{(3x  -  1)}{(2x  -  3)} \times \frac{(2x  -  3)}{(3x  -  1)}\)

= \(\frac{(3x  -  1)^{2}}{(2x  -  3)^{2}}\)

= \(\frac{9x^{2}  -  6x  +  1}{4x^{2}  -  12x  +  9}\)

 

6. Reduce the algebraic fraction to its lowest form:

 \(\frac{1}{x^{2}  -  3x  +  2}  +  \frac{1}{x^{2}  -  5x  +  6}  +  \frac{1}{x^{2}  -  4x  +  3}\)

Solution:

\(\frac{1}{x^{2}  -  3x  +  2}  +  \frac{1}{x^{2}  -  5x  +  6}  +  \frac{1}{x^{2}  -  4x  +  3}\)

= \(\frac{1}{x^{2}  -  2x  -  x  +  2}  +  \frac{1}{x^{2}  -  3x  -  2x  +  6}  +  \frac{1}{x^{2}  -  x  -  3x  +  3}\)

= \(\frac{1}{x(x  -  2)  -  1(x  -  2)}  +  \frac{1}{x(x  -  3)  -  2(x  -  3)}  +  \frac{1}{x(x  -  1)  -  3(x  -  1)}\)

= \(\frac{1}{(x  -  2)(x  -  1)}  +  \frac{1}{(x  -  3)(x  -  2)}  +  \frac{1}{(x  -  1)(x  -  3)}\)

= \(\frac{1 \times (x  -  3)}{(x  -  2)(x  -  1)(x  -  3)}  +  \frac{1\times (x  -  1)}{(x  -  3)(x  -  2)(x  -  1)}  +  \frac{1\times (x  -   2)}{(x  -  1)(x  -  3)(x  -  2)}\)

= \(\frac{(x  -  3)}{(x  -  2)(x  -  1)(x  -  3)}  +  \frac{(x  -  1)}{(x  -  3)(x  -  2)(x  -  1)}  +  \frac{(x  -  2)}{(x  -  1)(x  -  3)(x  -  2)}\)

= \(\frac{(x  -  3)  +  (x  -  1)  +  (x  -  2)}{(x  -  1)(x  -  2)(x  -  3)}\)

= \(\frac{(3x  -  6)}{(x  -  1)(x  -  2)(x  -  3)}\)

= \(\frac{3(x  -  2)}{(x  -  1)(x  -  2)(x  -  3)}\)

= \(\frac{3}{(x  -  1)(x  -  3)}\)

 

7. Simplify the algebraic fraction:

\(\frac{3x}{x  -  2}  +  \frac{5x}{x^{2}  -  4}\)

Solution:

\(\frac{3x}{x  -  2}  +  \frac{5x}{x^{2}  -  4}\)

= \(\frac{3x}{x  -  2}  +  \frac{5x}{x^{2}  -  (2)^{2}}\)

= \(\frac{3x}{x  -  2}  +  \frac{5x}{(x  +  2)(x  -  2)}\)

= \(\frac{3x \times (x  +  2)}{(x  -  2)(x  +  2)}  +  \frac{5x}{(x  +  2)(x  -  2)}\)

= \(\frac{3x(x  +  2)  -  5x}{(x  -  2)(x  +  2)}\)

= \(\frac{3x^{2}  +  6x  -  5x}{(x  -  2)(x  +  2)}\)

= \(\frac{3x^{2}  +  x}{(x  -  2)(x  +  2)}\)

= \(\frac{x(3x  +  1)}{(x  -  2)(x  +  2)}\)






8th Grade Math Practice

From Simplification of Algebraic Fractions to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.